PERKAWINAN JANDA TANPA AKTA CERAI DI KEPENGHULUAN KARYA MUKTI KECAMATAN RIMBA MELINTANG KABUPATEN ROKAN HILIR - Ahmad Sobari; Maryati Bachtiar; Riska Fitriani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
The relationship of marriage is intended to for life and happiness for the coupleconcerned. Keeping the purpose of marriage is likely to dispute that resulted in divorce.Divorce should be done at the trial court. Divorce can only be proven by a divorce certificateissued by the Court. Interest thesis: First, factor the cause of the marriage without divorcecertificate, Secondly, the legal consequences of marriage and divorce certificates widowswithout Third, legality Widow marriage without divorce certificates according to theMarriage Act and Islamic Law Compilation. This type of research is classified into types ofEmpirical Legal Research. The study was conducted in the village of Karya Mukti DistrictRimba Melintang of Rokan Hilir.Causes of the marriage without divorce certificates in the village of Karya Muktibecause, first, geography, Second, a lack of public understanding of marriage law. Effects ofmarriage without divorce the marriage certificate can be canceled, Children born still has alegal relationship with both parents. Community property marriage without divorcecertificates can not be divided. Widow marriage without divorce certificates according to theMarriage Act and Islamic Law Compilation unauthorized and may be canceled. SuggestionsAuthor, First, the Religious Court and the Office of Religious Affairs needs to improvedissemination to the public. Second, the Court of religion in order to continue the activitiesaround the marriage isbat to curb cooperation with the Office of Religious Affairs. Third,religious leaders and village officials in order to help the Religious Courts.Keywords: Marriage - Divorce - Divorce Certificate